[18F]Tetrafluoroborate, a new NIS PET/CT radiopharmaceutical: an overview focused on differentiated thyroid cancer - Arnoldo Piccardo; Francesco Fiz; Sergio Righi; Stefano Raffa; Mattia Riondato; Gianluca Bottoni; Matteo Bauckneht; Michela Massollo; Alessio Rizzo; Mehrdad Shoushtari Zadeh Naseri; Pierpaolo Trimboli; Giorgio Treglia (European Thyroid Journal)
Background: In relapsing differentiated thyroid cancer (DTC), the in vivo evaluation of natrium–iodide symporter (NIS) expression is pivotal in the therapeutic planning and is achieved by 131/123Iodine (131/123I) whole body scan. However, these approaches have low sensitivity due to the low resolution of SPECT. 18F-Tetrafluoroborate (TFB) has been proposed as a viable alternative, which could outperform 131/123I scans owing to the superior PET resolution. We have reviewed the literature to collect the available data on TFB diagnostic performance and compare it with the standard methods. Methods: Two authors searched PubMed, CENTRAL, Scopus, Web of Science and the web for studies evaluating the biodistribution and dosimetry of TFB in patients with DTC. General characteristics, technical parameters, procedures’ sensitivities and standards of reference were extracted from the selected studies. The risk of bias was evaluated with the QUADAS-2 scoring system. Results: Five studies were included in the review. Two analysed TFB’s biodistribution and dosimetry, while the other three assessed its diagnostic performance. The diagnostic comparators were 18F-FDG PET/CT (all cases), 124I-PET/CT (one study) and diagnostic/therapeutic 131I-SPECT/CT (one study each). TFB performed better than 131I; the TFB and 18F-FDG PET/CT combination achieved the best sensitivity. TFB delivered significantly less dose than the other NIS tracers. Conclusion: TFB is a promising tracer in relapsing DTC, showing higher sensitivity and less radiation exposure than the standard methods. The TFB and 18F-FDG combination appears particularly intriguing, especially when disease heterogeneity is suspected. However, data are still sparse and need to be confirmed by further investigations.